Miiuy Croaker Hepcidin Gene and Comparative Analyses Reveal Evidence for Positive Selection - Xu, Tianjun; Sun, Yuena; Shi, Ge; Wang, Rixin (PLOS ONE, 2012)
Hepcidin antimicrobial peptide (HAMP) is a small cysteine-rich peptide and a key molecule of the innate immune system against bacterial infections. Molecular cloning and genomic characterization of HAMP gene in the miiuy croaker (Miichthys miiuy) were reported in this study. The miiuy croaker HAMP was predicted to encode a prepropeptide of 99 amino acids, a tentative RX(K/R)R cleavage motif and eight characteristic cysteine residues were also identified. The gene organization is also similar to corresponding genes in mammals and fish consisting of three exons and two introns. Sequence polymorphism analysis showed that only two different sequences were identified and encoded two proteins in six individuals. As reported for most other species, the expression level was highest in liver and an up-regulation of transcription was seen in spleen, intestine and kidney examined at 24 h after injection of pathogenic bacteria, Vibrio anguillarum, the expression pattern implied that miiuy croaker HAMP is an important component of the first line defense against invading pathogens. In addition, we report on the underlying mechanism that maintains sequences diversity among fish and mammalian species, respectively. A series of site-model tests implemented in the CODEML program revealed that moderate positive Darwinian selection is likely to cause the molecular evolution in the fish HAMP2 genes and it also showed that the fish HAMP1 genes and HAMP2 genes under different selection pressures.